The Short Term Effect of Intravitreal Ranibizumab on Diabetic Macular Edema - Kobat, Sabiha Gungor; Celiker, Fatma Ulku (Karger, 2014)
[Abstract Not Available]
Keywords: Diabetic Macular Edema; Ranibizumab